Evaluación de impacto ambiental de los talleres de chapistería, ubicados en la ciudad de Puyo, a través del método de Conesa, para proponer un plan de manejo ambiental - Murillo Tacuri, Jeniffer Carolina (2015)
This work consisted in the diagnosis of 20 existing sheet metal workshops in the city of Puyo and the Environmental Impact Assessment methodology applying Conesa Cause - Effect, the Untapped and Painting Workshop New Generation and settled for alternative solutions development of clean production, using measures under environmental norms and laws established by the Ministry of Environment in force until the date the present study. It was determined that the presence of environmental impacts, mainly by poor enforcement and lack of processes washing, degreasing, caulking, preparing and painting, which are dangerous for the environment and human health. With this information it was determined that must be implemented in all body shops the Environmental Management Plan which is made up of different programs to prevent and mitigate environmental impacts, proper waste management, program communication, training and environmental education program contingencies, reclamation and closure or abandonment; integrating technical tools that would help owners of each of these establishments to become more competitive and meet the needs of the most demanding customers, being responsible with the environment and safety of people.